Arabisme-Persianisme : Sketsa Dialektika Islam dan Budaya Lokal - Fahrurrozi - (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2003)
This paper, the writer states that the Islam came to a region never away from the dialogue or the dialectic with the culture of the region. Islam as a religion and a revealation is the great tradition and it come to hold a dialogue with the little tradition (locality). Therefore, the culture or tradition is something unseparated with the Islamic religion. Arab is a culture. Historically, when Islam was born in Arab, it made a dialogue with the arabic culture, the arable Islam in the course of time then meet and held a dialogue with the Persian Civilization. So that, it produced the conversive civility, with the unsure of Islam, Arab, and Persia. The meeting between Islam as the universal teaching (great tradition) with Arab and Persia (little tradition) were the indication that a teaching of a religion can not be seperated with the cultural value whereas such religion developed and preached.